PENGARUH KINERJA LAYANAN DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN PEMASANG IKLAN - Rd. Muhammad Ridho; Syahmardi Yacob (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
The aim of this study is to analyze the influence of service performance and brand image on customer satisfaction partially and simultaneously. The population consists of 350 customers (advertisers) while sample size is 78 units. Methods of data collection used survey which is followed by statistical examination to test the hypothesis, used multiple linear regressions. The results showed that service performance and brand image have positive and significant influence on customer satisfaction, where brand image has a more dominant influence when compared to service performance variables.